THU0298 Type I Interferon Predicts Biological Effect of Belimumab on Rheumatoid Factor Positive B-Cells in Sjögren's Syndrome: Results from The Beliss Trial. (15th July 2016) - Quartuccio, L.; Mavragani, C.P.; Nezos, A.; Gandolfo, S.; Tzioufas, A.; De Vita, S.
Abstract : Background: B-lymphocyte Stimulator (BLyS, or BAFF), a survival factor for B cells, has been previously implicated in the pathogenesis of Sjögren's syndrome (SS) and SS related lymphoproliferation (1–2). It has been also previously shown to be induced by both type I and II Interferons (IFNs) also implicated in the pathogenesis of SS (3). Belimumab, an anti-BAFF monoclonal antibody that targets BAFF, was recently found to be effective and safe in SS in the phase II BELISS trial (4–5). Objectives: To explore the possible effect of belimumab on IFN-induced peripheral blood gene expression in the phase II BELISS trial. Additionally, to evaluate whether baseline IFN signature could serve as a predictor of clinical and serological responses following belimumab treatment. Methods: Twelve patients who were enrolled in the phase II BELISS trial were studied for peripheral blood IFN signature at baseline, at w28 (10/12), and at w52 (4/12). Patients were all females, median 47.5 yrs (35–79), all positive for anti-SSA/SSB and for rheumatoid factor (RF), with a median ESSDAI score of 7 (2–27) at BELISS study entry. Peripheral blood mononuclear cells from all study participants were subjected to Real-Time PCR for 3 interferon inducible genes (MX-1, IFIT-1, IFI44) preferentially induced by type I IFN and 2 interferon inducible genes preferentially induced by type II IFN (MIG-1, GBP1). Both type I and II IFN scores were determined, as previously described. Results: No statistically significant changes were observed between baseline and w28 or w52 type I IFN scores (mean±SE: 17.8±3.2 vs 19.9±3.7 vs 20.2±1.2, respectively, p>0.05 for all comparisons by paired sample t-tests). Baseline type I IFN scores were correlated with changes in rheumatoid factor from baseline to w52, baseline mental component score of SF-36 (r=0.7/p=0.007, and r=0.8/p=0.003, respectively, by Pearson's test). When patients were subdivided in two groups, i.e. low IFN score and high IFN score, based on the baseline mean of IFN score, a significant differences were found between low and high IFN score groups as regards baseline to w52 changes in IgG (p=0.004, by Mann-Whitney), IgA (p=0.004, by Mann-Whitney), IgM levels (p=0.03, by Mann-Whitney) in favour of high IFN score group, while changes in RF levels tended to be significant (p=0.08, by Mann-Whitney). No significant changes or associations with type II IFN scores were observed. Conclusions: Type I IFN-induced peripheral blood gene expression may affect the magnitude of biological effect of belimumab in SS, and in particular on RF-positive B-cell clones. Patients showing higher IFN signature may be the optimal target for belimumab in SS. References: Quartuccio L, et al. Rheumatology 2013;52:276–81. Papageorgiou A, et al. Arthritis Rheumatol. 2015;67:2732–41. Nezos A, et al. J Autoimmun. 2015;63:47–58. Mariette X, et al. Ann Rheum Dis. 2015;74:526–31. De Vita S, et al. Rheumatology 2015;54:2249–56. Disclosure of Interest: None declared